Characterization of isopropanol-enhanced Caesalpinia bonduc biodiesel blends: A sustainable strategy for decarbonization - D. Christopher selvam; Yuvarajan Devarajan; T. Raja (Results in Engineering)
This research endeavor examines the viability of methyl ester derived from Caesalpinia bonduc seeds as a sustainable substitute for traditional diesel fuel. The investigation primarily concentrates on tackling the dual imperatives of diminishing dependence on fossil fuels and bolstering decarbonization initiatives through the conversion of non-edible Caesalpinia bonduc seed oil into biodiesel via a two-stage transesterification methodology. The resultant biodiesel formulations were augmented with isopropanol at proportions of 10% and 20% to enhance combustion efficiency and emissions characteristics.Experimental assessment of the formulations indicated notable enhancements in Brake Thermal Efficiency (BTE) alongside reductions in Brake-Specific Fuel Consumption (BSFC), coupled with substantial declines in carbon monoxide (CO), hydrocarbon (HC), and particulate emissions when juxtaposed with pure biodiesel. The most effective formulation, designated as CBOBD80I20, exhibited an optimal equilibrium between improved performance metrics and diminished emissions. While a marginal rise in nitrogen oxide (NOx) emissions was noted, the concentrations remained within permissible thresholds.This investigation underscores the potential of isopropanol-enhanced biodiesel formulations to function as a feasible and ecologically sustainable alternative to conventional diesel fuel. Furthermore, it accentuates the necessity for continued research into the long-term operational efficacy of engines and cost optimization strategies to promote widespread implementation and advance sustainable energy paradigms.